WEAR MONITORING OF INSERT TYPE MILLING TOOL BY IMAGE PROCESSING TECHNIQUE - Devanshi A Jhaveri; Prof. Rahul Annapanyawar (International Journal of Innovations in Engineering Research and Technology, 2021)
Strong competition forces companies implement various productivity improvement efforts. Tool wear measurement is of great importance in machining industry, as affects the surface quality, dimensional and production costs of the material components. has been developed in this study vision system based on digital image processing for the measurement of tool wear. Tool wear images were captured andimage. In order to increase the lead time (ie, minimization of wear of the tool) and to remove more material for the required surface roughness in machining parameters such as speed, feed and depth of cut should be optimized. Optimization has great cal significance especially for editing. to this result an approach based on overall equipment effective